Factors of Risk in the Development of Cerebrovascular Disease in Akita: Comparison of epidemiological study between two towns - Kotoku, Toshimitsu; Nakamura, Takashi; Watanabe, Katsuhiro; Ito, Keiichi; Kutsuzawa, Takashi; Oyama, Keiko; Iwabuchi, Takayuki (Nippon Ronen Igakkai Zasshi. Japanese Journal of Geriatrics, 1972)
To study factors responsible for the development of cerebrovaseular disease (CVD), comparison of cross-sectional population survey was performed in two neighboring towns in Akita prefecture, Yuwa and Tenno, where the age-adjusted death rates of CVD were significantly different. The death rates of CVD were 361/100, 000 population in Yuwa and 219/100, 000 population in Tenno. The results obtained in two towns were as follows. 1) Yuwa population trended to have the higher systolic blood pressure than Tenno. This was particulary significant in the fourth decade for males, and in the fourth to seventh decades for females. 2) On ECG, the findings of left ventricular hypertrophy, which might be attributed to hypertension, were more frequently observed in the fourth, sixth and seventh decades of Yuwa population. 3) There were no differences in the values of serum cholesterol, phospholipid and triglycerides between two towns. 4) The ratios of linoleic acid to oleic acid (L/O) were significantly lower in the fourth to seventh decades for males and in the fourth to fifth decades for males in Tenno, where the deaths of CVD were lower than in Yuwa. 5) Serum uric acid was higher in fourth to seventh decades for males and in the fourth to fifth decades for females in Tenno. This may be due to differences in taking of dietary protein and fat between Tenno and Yuwa. 6) The frequency of the calcification in the carotid siphon observed on the plain skull radiogram increased with ages in both towns. There were no differences in the frequency of the calcification of the carotid siphon and the sclerotic changes of the ocular fundi between two towns. These results suggest that abnormalities of serum lipid, which has been considered as risk factors for CVD, may not be of predictive value with regard to the development of CVD in Akita. On the other hand, it was assurmed that the most potent factor responsible CVD might be the rising of the blood pressure.